2017
DOI: 10.1002/jcp.25918
|View full text |Cite
|
Sign up to set email alerts
|

Gax suppresses chemerin/CMKLR1‐induced preadipocyte biofunctions through the inhibition of Akt/mTOR and ERK signaling pathways

Abstract: Adipose tissue is closely associated with angiogenesis and vascular remodeling. Chemerin is involved in inflammatory reaction and vascular dysfunction. However, the mechanisms of chemerin participating in vascular remodeling and whether Growth arrest-specific homeobox (Gax) can effectively intervene it remain obscured. Here, 3T3-F442A preadipocytes were cultured, injected into athymic mice to model fat pads, and treated respectively with Adchemerin, Ad-Gax, or specific inhibitors in vitro and in vivo. MTT, flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…To explore the mechanism of chemerin promoting osteogenic differentiation, we detected the downstream molecules of chemerin signaling (Figure S4a, b; Inci et al, 2016; Jiang et al, 2018). We found Akt signaling decreased in Rarres2 −/− mice bone (Figure 6a, b) and increased in TG mice bone (Figure 6c, d).…”
Section: Resultsmentioning
confidence: 99%
“…To explore the mechanism of chemerin promoting osteogenic differentiation, we detected the downstream molecules of chemerin signaling (Figure S4a, b; Inci et al, 2016; Jiang et al, 2018). We found Akt signaling decreased in Rarres2 −/− mice bone (Figure 6a, b) and increased in TG mice bone (Figure 6c, d).…”
Section: Resultsmentioning
confidence: 99%
“…Note that Sal B lifted p‐ERK to activate the MEK‐ERK pathway and increase TAZ expression. The MEK‐ERK signalling pathway has been intensively investigated in regulating cells differentiation . Jaiswal et al have suggested that the commitment of human MSCs into osteogenic or adipogenic lineages was governed by activation or inhibition of ERK1/2, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…2007 ). The activation of chemerin-CMKLR1 axis facilitates the proliferation and differentiation of preadipocytes by inducing the AKT-mTOR and ERK signalling cascade ( Jiang et al . 2018 ).…”
Section: The Role Of Chemerin In Energy Balance Regulation and Obesitmentioning
confidence: 99%
“…Concomitant with the enhancement of preadipocyte differentiation, chemerin overexpression upregulates VEGF that promotes vascular endothelial cell proliferation, differentiation and angiogenesis in the cultured cells. Moreover, the vascular intensity in the fat pad is increased by the overexpression of chemerin ( Jiang et al . 2018 ), suggesting that chemerin boosts angiogenic potential of fat tissues.…”
Section: The Role Of Chemerin In Energy Balance Regulation and Obesitmentioning
confidence: 99%